The inexplicable logic of my life a novel - Sáenz, Benjamin Alire 1954- (Clarion Books, Houghton Mifflin Harcourt, 2017)
"A story set on the American border with Mexico, about family and friendship, life and death, and one teen struggling to understand what his adoption does and doesn't mean about who he is"...